Gambaran Pelaksanaan Mobilisasi Dini Dalam Penurunan Skala Nyeri Pada Ibu Post Sectio Caesarea di RSUD Ciamis - Tetet Kartilah; Peni Cahyati; Sofia Februanti; Sofiatul Kamila; Kusmiyati Kusmyiati (STIKes Karsa Husada Garut, 2022)
SC surgery can help the mother give birth if the mother is unable to give birth pervaginam or normally. But physically, the mother will feel pain due to the tearing of tissues in the walls of the abdomen and uterus. Pain is the most common problem experienced by post partum SC mothers. This form of pain management can be done by early mobilization. The purpose of the study was to provide an overview of the implementation of early mobilization in reducing the scale of pain in post sectio caesarea mothers. This type of research design is descriptive with a case study approach to explore the pain response of post partum SC mothers who get early mobilization interventions. The study was conducted on two post partum sectio caesarea mothers. The results showed that both respondents mobilized well and experienced a decrease in the scale of pain after conducting early mobilization interventions. The high level of motivation is a factor that affects the implementation of early mobilization and affects the decrease in the scale of pain. Meanwhile, the inhibiting factor in reducing the pain scale is the low patient's knowledge about the importance of pain management by conducting early mobilization. To improve services in providing effective nursing care, the health service is expected to increase knowledge, provide motivation and supervise the implementation of mobilization in post partum sectio caesarea mothers to accelerate the reduction of pain scale.